Reliability and Validity Evaluation of the RAT-43 Psychological Resilience Scale in Chinese Adolescents - Jing, Chen; Amalia, Madihie (CANA, 2025)
Objectives: To assess the level of psychological resilience among Chinese college students, this study introduces the Resilience Assessment Tool 43 (RAT-43), developed by Amalia bt Madihie and Siti Norazilah Mohd Said. Based on the "Magic Box Model" [2], the tool encompasses five dimensions: foundation, belonging, learning, coping, and core self, and has demonstrated good reliability and validity in countries such as Malaysia and Iran (Amalia, 2017). However, the applicability of RAT-43 in the Chinese college student population has not been thoroughly investigated.